Analisis Gender terhadap Perbedaan Kepercayaan Diri dan Regulasi Emosi Siswa Siswi di SMKN 7 Surakarta - Ulyaa, Laely Shifatul; Anniez Rachmawati; Sri Ernawati (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the differences in self-confidence and emotional regulation based on gender among students at SMKN 7 Surakarta. Self-confidence and emotional regulation are crucial aspects in the psychological dynamics of adolescents, often influenced by social constructs, including gender roles. In this context, gender can affect how students build their self-confidence and manage emotions in various life situations, particularly in school. This research uses a qualitative approach with a case study method to delve into the subjective experiences of male and female students through in-depth interviews and participatory observation. The informants in this study consisted of 12 students, purposively selected based on the consideration of the guidance counselor (BK) and gender characteristic variations in the class. The results show that female students tend to be more open in expressing emotions and have more adaptive emotional regulation abilities. Female students are better at identifying, regulating, and expressing their feelings in a healthier way in various social and academic situations. On the other hand, male students exhibit higher self-confidence in academic and achievement contexts, but they tend to suppress emotional expression due to the pressure of masculinity norms in society. Males are often taught not to show emotions, which affects how they manage their feelings in daily life and social interactions. This study reveals that gender differences influence how students build self-confidence and regulate emotions in the school environment. Female students are more open and adaptive in emotional regulation, while male students excel in academic self-confidence but tend to be more emotionally closed. These findings have important implications for the development of gender-sensitive counseling programs that address the emotional needs of students, aiming to create a school environment that supports the psychological development of all students in a balanced way, while providing space for healthy emotional expression for both genders.